2017
DOI: 10.4049/jimmunol.1600583
|View full text |Cite
|
Sign up to set email alerts
|

Selective IRAK4 Inhibition Attenuates Disease in Murine Lupus Models and Demonstrates Steroid Sparing Activity

Abstract: The serine/threonine kinase IL-1R–associated kinase (IRAK)4 is a critical regulator of innate immunity. We have identified BMS-986126, a potent, highly selective inhibitor of IRAK4 kinase activity that demonstrates equipotent activity against multiple MyD88-dependent responses both in vitro and in vivo. BMS-986126 failed to inhibit assays downstream of MyD88-independent receptors, including the TNF receptor and TLR3. Very little activity was seen downstream of TLR4, which can also activate an MyD88-independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…Our data show that IRAK4 controls the activation of IKK␤ to activate IRF5 but not NFB. Of note, and entirely consistent with our results, Dudhgaonkar et al (34) recently demonstrated inhibition of IKK␤ phosphorylation and cytokine release from TLR ligand stimulated human PBMC using an undisclosed highly potent and selective IRAK4 inhibitor, but did not present data regarding NFB. IKK␤ is thought to be the canonical activator of NFB, yet our data demonstrate that NFB is minimally affected with IRAK4 kinase inhibition in R848-treated human monocytes, as is phosphorylation and degradation of IB.…”
Section: Ikk␤ Activates Irf5 But Not Nfb In Tlr Signalingsupporting
confidence: 92%
“…Our data show that IRAK4 controls the activation of IKK␤ to activate IRF5 but not NFB. Of note, and entirely consistent with our results, Dudhgaonkar et al (34) recently demonstrated inhibition of IKK␤ phosphorylation and cytokine release from TLR ligand stimulated human PBMC using an undisclosed highly potent and selective IRAK4 inhibitor, but did not present data regarding NFB. IKK␤ is thought to be the canonical activator of NFB, yet our data demonstrate that NFB is minimally affected with IRAK4 kinase inhibition in R848-treated human monocytes, as is phosphorylation and degradation of IB.…”
Section: Ikk␤ Activates Irf5 But Not Nfb In Tlr Signalingsupporting
confidence: 92%
“…On the other hand, activation of autophagy favors plasmablast development, enabling expansion of self-reactive B cells in SLE, as well as type I IFN production by facilitating intracellular IC transport [ 41 , 42 ]. These observations merit further studies of the effects of I92 on different cell types, not least considering that IRAK4 inhibition ameliorates experimental murine lupus, suggesting a favorable effect also in human SLE [ 43 ]. Translating results of in-vitro studies of pharmaceutical compounds to potential drug effects in vivo has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…3 ) and, therefore, is a prime target candidate for the treatment of several inflammatory diseases 59 61 , 74 . Mutations in the kinase domain in IRAK4 that abrogate its activity protect mice in several inflammatory disease models, including septic shock 63 , 75 77 , SLE 78 80 , acute liver injury 81 , cardiovascular disease 82 and the APPPS1 Alzheimer disease model 83 .…”
Section: Irak1 and Irak4mentioning
confidence: 99%